The separation of malic dehydrogenase isoenzymes of Neurospora crassa by polyacrylamide gel electrophoresis - M. V. Laycock; H. G. Kolmark; D. Boulter (Fungal Genetics Reports, 1963)
The separation of malic dehydrogenase isoenzymes of Neurospora crassa by polyacrylamide gel electrophoresis